Psychology and open science in Africa: Why is it needed and how can we implement it? - Azouaghe, Soufian; Adetula, Adeyemi; Forscher, Patrick; Basnight-Brown, Dana; Ouherrou, Nihal; Charyate, Abdelilah; Ijerzman, Hans (My University, 2020)
The quality of scientific research is assessed not only by its positive impact on socio-economic development and human well-being, but also by its contribution to the development of valid and reliable scientific knowledge. Thus, researchers regardless of their scientific discipline, are supposed to adopt research practices based on transparency and rigor. However, the history of science and the scientific literature teach us that a part of scientific results is not systematically reproducible (Ioannidis, 2005). This is what is commonly known as the "replication crisis" which concerns the natural sciences as well as the social sciences, of which psychology is no exception. Firstly, we aim to address some aspects of the replication crisis and Questionable Research Practices (QRPs). Secondly, we discuss how we can involve more labs in Africa to take part in the global research process, especially the Psychological Science Accelerator (PSA). For these goals, we will develop a tutorial for the labs in Africa, by highlighting the open science practices. In addition, we emphasize that it is substantial to identify African labs needs and factors that hinder their participating in the PSA, and the support needed from the Western world. Finally, we discuss how to make psychological science more participatory and inclusive.
Keywords: African Research; Credibility Revolution; Open Science; Psychological Science Accelerator; Replication Crisis